Features of computer games dedicated to the war in Ukraine - Berezhna, O. B. (ТОВ «Друкарня Мадрид», 2024)
In today's world, gaming is becoming not only an entertainment for mat, but also a media tool for shaping worldviews and showing empathy. The topic of games dedicated to the war in Ukraine and their impact on public opinion deserves special attention. Games, as a media form of expression, can evoke emotional reactions andinfluence the perception of events that occur in the real world.
Keywords: computer; games